1984
DOI: 10.1083/jcb.99.3.971
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of sodium- and potassium-activated adenosinetriphosphatase in HeLa cells by ouabain step selection.

Abstract: A multistep selection for ouabain resistance was used to isolate a clone of HeLa S3 cells that overproduces the plasma membrane sodium, potassium activated adenosinetriphosphatase (Na+,K+-ATPase). Measurements of specific [3H]ouabain-binding to the resistant clone, C+, and parental HeLa cells indicated that C+ cells contain 8-10 X 10(6) ouabain binding sites per cell compared with 8 X 10(5) per HeLa cell. Plasma membranes isolated from C+ cells by a vesiculation procedure and analyzed for ouabain-dependent inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…The increase in Na,K-ATPase content of C+ cells was correlated with the appearance of minute chromosomes, a hallmark of gene amplification (15). The reversion of C+ cells to ouabain sensitivity, coupled with a decrease in Na,K-ATPase and a loss of minute chromosomes (1,12), suggested that Na,K-ATPase overproduction in C+ cells was associated with gene amplification.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The increase in Na,K-ATPase content of C+ cells was correlated with the appearance of minute chromosomes, a hallmark of gene amplification (15). The reversion of C+ cells to ouabain sensitivity, coupled with a decrease in Na,K-ATPase and a loss of minute chromosomes (1,12), suggested that Na,K-ATPase overproduction in C+ cells was associated with gene amplification.…”
mentioning
confidence: 93%
“…One such cell line, C+, was found to express a 10-fold-higher level of Na,K-ATPase than parental HeLa cells (1,12). The increase in Na,K-ATPase content of C+ cells was correlated with the appearance of minute chromosomes, a hallmark of gene amplification (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ouabain-binding measurement and calculation of the number of ouabain-binding sites were performed as previously described (1).…”
Section: Methodsmentioning
confidence: 99%
“…A variant of the HeLa S3 cell line which expressed 10-to 12-fold more ouabain-binding sites was recently selected with the sodium-and potassium-activated ATPase (Na+,K+-ATPase) inhibitor ouabain (1). The unstable ouabainresistant phenotype was correlated with the presence of minute chromosomes, and amplification of the gene for Na+,K+-ATPase was proposed as the mechanism leading to drug resistance.…”
mentioning
confidence: 99%